The sanatorium eaudiobook - Pearse, Sarah (Detective Elin Warner, 2021)
REESE'S BOOK CLUB PICK | An instant New York Times bestseller! A page-turning thriller from the author of The Retreat. “An eerie, atmospheric novel that had me completely on the edge of my seat.” — Reese Witherspoon “This spine-tingling, atmospheric thriller has it all… and twists you’ll never see coming.” —Richard Osman, New York Times bestselling author of The Thursday Murder Club You won't want to leave. . . until you can't. Half-hidden by forest and overshadowed by threatening peaks, Le Sommet has always been a sinister place. Long plagued by troubling rumors, the former abandoned sanatorium has since been renovated into a five-star minimalist hotel. An imposing, isolated getaway spot high up in the Swiss Alps is the last place Elin Warner wants to be. But Elin's taken time off from her job as a detective, so when her estranged brother, Isaac, and his fiancée, Laure, invite her to celebrate their engagement at the hotel, Elin really has no reason not to accept. Arriving in the midst of a threatening storm, Elin immediately feels on edge—there's something about the hotel that makes her nervous. And when they wake the following morning to discover Laure is missing, Elin must trust her instincts if they hope to find her. With the storm closing off all access to the hotel, the longer Laure stays missing, the more the remaining guests start to panic. Elin is under pressure to find Laure, but no one has realized yet that another woman has gone missing. And she's the only one who could have warned them just how much danger they are all in. . .